IMPROVING ELEMENTARY STUDENTS' VOCABULARY MASTERY THROUGH EDUCATIONAL ENGLISH VIDEOS: A STUDY IN MORAMO - Arsih Wahyuni; Andi Rachmawati Syarif; Faridawati Faridawati; Eko Saputra Nurdiansa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
English language skills is becoming increasingly vital in today's globalized world. Proficiency in vocabulary is essential for language acquisition since it improves students' conversational abilities and academic achievement. The purpose of this study is to assess the impact of educational English videos in promoting vocabulary acquisition among primary school pupils in Moramo. The study was conducted with one class of 16 grade five pupils at SDN 8, Moramo. Using a one-group pretest-posttest design that included 15 numbers of the pre-test. Data analysis revealed that the mean post-test score exceeded the mean pre-test score, with averages of 7.18 for the pre-test and 9.43 for the post-test. Statistical analysis using a paired sample t-test showed an improvement of 2.25 points in student performance after the test. The results of the paired sample t-test showed a significance value of 0.00 (p < 0.05), which means there is a significant difference between before and after the treatment. Therefore, it can be concluded that the alternative hypothesis (H1) is accepted, meaning the use of English educational videos significantly improved vocabulary achievement among primary school students in Moramo.